2018
DOI: 10.1111/bju.14170
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative outcomes and complications after laparoscopic vs robot‐assisted dismembered pyeloplasty: a systematic review and meta‐analysis

Abstract: For patients with PUJ obstruction, our meta-analyses show that RAP is advantageous concerning operating time, length of hospital stay, complication rate and success rate. Our conclusions, however, are weakened by poor quality of evidence and significant study heterogeneity. In addition, whether the statistical significance observed in the present meta-analysis translates into clinical significance is an important question. Further high-quality studies, particularly randomized controlled trials, are necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
0
30
1
Order By: Relevance
“…The learning curve considered significant, where a study reported a shortening of operative time in line with experience. 12 In contrast to the length of operation, the normal intraoperative bleeding in this study was 50 ml, slightly more bleeding than another study with 20 mL for the average blood loss. 11 Our data shows a wide range of intraoperative bleeding volume, as the first case of LP in our centre, reached 500 mL of intraoperative bleeding.…”
Section: Discussioncontrasting
confidence: 65%
“…The learning curve considered significant, where a study reported a shortening of operative time in line with experience. 12 In contrast to the length of operation, the normal intraoperative bleeding in this study was 50 ml, slightly more bleeding than another study with 20 mL for the average blood loss. 11 Our data shows a wide range of intraoperative bleeding volume, as the first case of LP in our centre, reached 500 mL of intraoperative bleeding.…”
Section: Discussioncontrasting
confidence: 65%
“…There have been several reports comparing RALP with LP, but no reports that compared the three different procedures, including RALP, LESS‐P and LP, in which a single surgeon operated on adults …”
Section: Patient Background and Resultsmentioning
confidence: 99%
“…In contrast, suturing is known to be challenging in LESS‐P, as it has limited working space . Although RALP might have a learning curve, it has also been reported that experience with LP contributes to a reduction of the learning curve for RALP . It is expected that the time can be shortened through experience of more robotic procedures.…”
Section: Patient Background and Resultsmentioning
confidence: 99%
See 2 more Smart Citations